Diskrimineringsansvar : En civilrättslig undersökning av förutsättningarna för ansvar och ersättning vid diskriminering - Hellborg, Sabina (Iustus förlag, 2018)
This doctoral thesis examines liability for discrimination under Swedish private law. According to chapter 5, section 1 of the Swedish Discrimination Act (diskrimineringslagen) compensation shall be paid by natural or legal persons who violate the prohibitions of discrimination that are established in the act. The purpose of the compensation is not only to compensate the person discriminated against for the violation of the right to equal treatment, but also to prevent further discrimination. The thesis examines two main questions: (i) what preconditions need to be fulfilled in order to establish liability for discrimination? and (ii) what circumstances affect the amount of compensation? An overarching aim of the thesis is to create an understanding of the characteristic problems and questions that occur when handling discrimination-related questions in a private law context. Consideration is taken to the EU law background and the aim, articulated in EU directives, to achieve effective, proportionate and dissuasive remedies for breaches of the principle of equal treatment. The research focuses on the prohibitions applicable in the working life and regarding goods, services and housing. It includes detailed analyses of the prohibitions against direct discrimination, indirect discrimination, inadequate accessibility, harassment and sexual harassment. The analyses deal with questions concerning the subjective motives of the discriminating party, problematic aspects considering the burden of proof as well as the exceptions from the prohibitions. Circumstances affecting the amount of compensation are analysed considering the character of the discriminating behaviour and its effects. Certain aspects attributable to the preventive function of the damages are examined, as well as how they have been decisive in the court judgements.
Keywords: Ansvarsrätt; Diskriminering; Diskrimineringsersättning; Kränkning; Skadestånd; Skadeståndsrätt; Trakasserier

Institutionella samspel : Om möten mellan en kommersiell och en ideell logik - Kvarnstrom, Emilia (Företagsekonomiska institutionen, Uppsala universitet, 2016)
Institutional logics create order and stability. They organize interaction and prescribe how we should behave towards each other. Such logics have generally been regarded as exclusive, in the sense that an organizational field is always guided by a single institutional logic. If there are two or more institutional logics in one setting at the same time this will create conflicting demands and contradictions. So how do organizations and individuals that act in these settings, where different institutional logics do meet, cope with the conflicting demands? This question is researched by studying actors who organize partnerships between corporations and non-profit organizations. Institutional logics have typically been studied at field level. My study follows a more recent literature strand focusing on individuals and their way of coping with conflicting institutional logics. In this thesis, interviews, text analysis and observations are used. The interviews were conducted with CSR managers of corporations, managers of corporate partners at non-profit organizations, CSR consultants, and project managers of intermediary organizations. These actors are working in an environment where conflicting institutional logics are played out. Using a narrative approach it is shown how these actors are aware of their institutional environment and its conflicts which requires them to constantly act as translators. The study shows that the actors organize an interplay between a market-logic and a social-welfare logic by bringing together the logics and establishing limits to what extent logics can be mixed. Thus, the actors can be understood as bilingual, rather than hybrids. Furthermore, it is argued that a narrative approach provides the possibility to understand institutional logics in empirical contexts as more present and visible than they are usually considered to be. The study concludes that bilingual actors balance conflicting demands and negotiate requirements set by institutional logics in their day-to-day work. Settings where institutional logics meet can hence be understood as both a contradiction and an ongoing interplay.
Keywords: Actor; Cross-sectoral partnerships; Hybrid organization; Institutional logics; Institutional theory; Narrative; Partnerships

Ömsesidiga överenskommelser enligt skatteavtal - Sallander, Ann-Sophie (Jönköping International Business School, 2013)
Ömsesidiga överenskommelser (eng. mutual agreement procedures) återfinns huvudsakligen i artikel 25 OECD:s modellavtal. Syftet med sådana överenskommelser är att undvika internationell dubbelbeskattning. Överenskommelserna kan antingen utgöra ett rättsmedel, som är ett alternativ till domstolsförfarande, eller verka som ett medel för att få skatteavtalen att fungera bättre mellan de avtalsslutande staterna. De rättsliga svårigheter som uppkommer i samband med överenskommelserna beror huvudsakligen på att överenskommelserna utgör en internationellt, av OECD, konstruerad företeelse som ska anpassas till och tillämpas på ett nationellt, redan befintligt regelsystem. Det kan härmed uppkomma spänningar och motsättningar mellan olika bestämmelser. Det övergripande syftet med denna studie är att kartlägga och utvärdera en internationellt konstruerad företeelse, dvs. ömsesidiga överenskommelser, för att undersöka om ändamålet med sådana överenskommelser uppfylls inom ramen för det svenska regelsystemet. Studien företas inom rättsområdet internationell skatterätt, men har emellertid en interdisciplinär ansats. Härav analyseras även bestämmelser inom folkrätt, konstitutionell rätt, förvaltningsprocessrätt, allmän förvaltningsrätt och sekretess. The focal point of this study is mutual agreement procedures, which are found in tax treaties, and derived from Art. 25 OECD Model Tax Convention (OECD MTC). The overall purpose of the mutual agreements is to avoid international double taxation. The agreements can either constitute an alternative to court proceedings, or constitute a means for improving the functioning of tax treaties. Provisions regarding mutual agreements can be found, in various forms, in all Swedish tax treaties. Since Sweden is a dualistic state tax treaties are incorporated into the Swedish legal system by legislation. This means that the provisions regarding mutual agreements are incorporated into Swedish legislation. Legal difficulties that arise regarding the agreements are mainly due to the fact that mutual agreement procedures constitute an internationally, by the OECD, constructed phenomenon, which is to be applied on a nationally, already existing, legal system. It may hereby occur tensions and conflicts between different provisions. The overall aim of this study is to identify and evaluate mutual agreements from a Swedish perspective. This includes identifying a relatively unexplored area, i.e. mutual agreements and their place within the Swedish legal system. In order to meet the overall objective, three research tasks are formulated. First, which internal provisions apply to mutual agreements, and how are they to be applied? Secondly, it is examined if the Swedish legal system, regarding mutual agreements, is consistent from three evaluation criteria: the constitutional principles of separation of powers and legal competence, legal certainty aspects, and the provisions of the Vienna Convention of the Law on treaties (VCLT). If there are any inconsistences in the legal system, may these be solved? Thirdly, it is studied if the Swedish legal system, regarding mutual agreements, provides for fulfillment of the purpose of mutual agreements or if there are any legal obstacles to this. The thesis is carried out in the field of tax law. However, the study has an interdisciplinary approach, which means that aspects of other areas of law are considered, such as international law, constitutional law, administrative judicial procedural law, administrative law, and secrecy.
Keywords: Convention fiscale; Model Tax Convention; Mutual Agreement Procedure (MAP); Tax treaties